Penerjemahan Kata Budaya dari Novel Entrok (2010) Ke Dalam the Years of the Voiceless (2013) - Khairiah, Dewi (Paradigma: Jurnal Kajian Budaya, 2018)
This research on translation problems aims to examine the translation of cultural words in the novel Entrok (2010) into The Years of the Voiceless (2013). This research was conducted by applying qualitative and functional approaches, while the data were analyzed by applying Williams and Chesterman’s causal comparative model to identify the translation procedures which were applied to fulfill the available skopos. Based on Newmark’s categorization of cultural words, the researcher identified 80 cultural words which were categorized into three general groups: (1) material culture; (2) social culture and leisure; and (3) organization, customs, procedure, activity, and concept. The data were collected through library research and an interview with the translator. The researcher then used the causal comparative technique to compare between cultural words contained in the source text and their respective equivalents, and to analyze the translation procedures chosen by the translator to fulfill the skopos. There are four translation problems found in this research: (1) an SL concept and referent does not have the same TL concept and referent, (2) an SL concept and referent is not lexicalized in TL, (3) TL lacks of specific words, and (4) SL and TL have different ways of viewing a referent. To deal with those translation problems, the translator applied nine procedures consisting of explicitation, generalization, literal equivalent, calque, couplet (transference and footnote, transposition and cultural equivalent, and transposition and functional equivalent), cultural equivalent, descriptive equivalent, functional equivalent, and transference. The skopos was fulfilled through the application of translation procedures by taking account of ST context. According to a number of TT readers, the translator is considered successful in maintaining the author’s language style and producing the atmosphere of the source culture. The use of footnotes helps TT readers to understand ST cultural words better, but it also reduces the readers’ comfort in reading the TT.